Cultural expertise of culture resources - V. I. Panchenko (Ukrainian Cultural Studies, 2018)
The article studies cultural expertise, importance of which grows within conditions of social and cultural transformations in modern society. It is underlines the features of cultural expertise for the analysis and solution of social problems. Cultural expertise is the basis for different projects: cultural, urban, artistic. Cultural studies mean cumulative knowledge for the expert knowledge. Expert assessments of processes and objects, which cannot be calculated, are based on their own judgments. Cultural expertise includes analysis of social reality: values, public opinion, interests, traditions and rules. All this must be expressed in quantitative terms. The question of the appropriateness for using axiological parameters is still open. It is stressed that the cultural expertise is important on different stages of the project making activity: planning, support, implementation, evaluation of its effectiveness. At the national level decision-making procedure should include the recommendations of academic experts for the objective information and understanding the results that will be achieved in the future. The procedure of cultural expertise legitimizes state decisions for the society. Cultural resources of cities and regions are assets for creative economy implementation. Cultural expertise of culture resources is a main component in the process of this realization on the national level. Cultural, educational and regional policies in Ukraine should consider cultural studies knowledge as basic for cultural expertise, which can be seen as an instrument in the context of social reality. An important task of the cultural expertise is the correlation between existing and desired image of the city with its cultural potential. The image is constructed purposefully; it represents the desired vision of the city and social relation to it. The successfully created image is capable to transform the idea and the mission of the city from the "model" to the program of activities.
Keywords: cultural project, cultural expertise, cultural policy, expert evaluation, creative economy, cultural resources, urban policy